THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE TOWARDS EMPLOYEES’ PERFORMANCE WITH WORK MOTIVATION AS A MEDIATING VARIABLE ON EMPLOYEES OF FIF AMBON BRANCH DURING THE COVID-19 PANDEMIC - Rachma Attamimi; Harvey Hiariey (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
This research aims to analyze the effect of transformational leadership style on employees’ performance with work motivation as a mediating variable. The population in this research are all employees of PT. Federal International Finance, Ambon Branch, located at Jln Dr. Soetomo, Honipopu Village, Sirimau District. The sample used in this research amounts to 37 employees. The analysis tool used is Partial Least Square (PLS). Transformational leadership style has a positive effect on employee work motivation. The results also prove that work motivation has a positive effect on employees’ performance. Furthermore, transformational leadership style has a positive effect on employees’ performance mediated by employee work motivation.